Luteolin-7-O-glucoside from Elsholtzia ciliata extract inhibits the replication of coronavirus - Siyun Lee; Jang Hoon Kim; Chansoo Kim; WooChul Jung; Jayhyun Park; Junsoo Park (PLoS ONE, 2025)
Coronaviruses are RNA viruses with a high mutation rate that cause many human diseases, from severe COVID-19 to mild common cold. Therefore, discovering various medicines is required to reduce the symptoms of coronavirus infection. This report showed that the ethanol extract of the aerial parts of Elsholtzia ciliata (ECE) and its constituents can inhibit HCoV-OC43 (Human Coronavirus OC43) replication. HCoV-OC43, a human betacoronavirus genetically related to SARS-CoV-2, was used as a surrogate virus under BSL-2 conditions. To evaluate the antiviral properties of ECE, viral RNA levels were quantified using qRT-PCR, and viral protein expression was analyzed through Western blotting. ECE reduced coronavirus-induced plaque formation and viral RNA and protein expression in coronavirus-infected cells and conditioned media. Additionally, this was confirmed to have an inhibitory activity on virus production and improved cytopathic effects. ECE showed no cytotoxicity up to 40 µg/mL in vitro. As Elsholtzia ciliata has traditionally been consumed as a tea, oral administration could be a suitable route for further in vivo investigation. The main components of ECE were revealed by HPLC analysis and were isolated into four single compounds 1–4. Among them, luteolin-7-O-glucoside was effective in inhibiting the replication of coronavirus. Luteolin-7-O-glucoside demonstrated greater antiviral activity than ECE, with an estimated IC50 of 2 µM (around 1 µg/mL) compared to 5 µg/mL for ECE. This finding suggests that luteolin-7-O-glucoside could be a key contributor to the antiviral activity of the ECE. Finally, these results collectively suggest that Elsholtzia ciliata can be used as a potential antiviral treatment.